Ghrelin Levels in Patients with Rickets - Sen, Yasar; Demirol, Mustafa; Demirol, Hatice; Erman, Fazilet; Kilic, Nermin; Aydin, Suleyman; Cimbek, Emine Ayca (Modestum Ltd, 2013)
Rickets is a common metabolic bone disease in infants. The predominant cause of rickets is vitamin D deficiency. Vitamin D is required for bone formation. The role of ghrelin in bone metabolism is unclear, but it may have an indirect effect. There are also reports in the literature suggesting that ghrelin acts directly on osteoblasts as a positive regulator. To evaluate the relationship between ghrelin levels and the development of rickets. We evaluated the relationship between serum/saliva ghrelin levels and rickets in a cohort of 10 patients aged 6-24 months with nutritional rickets and completely healthy 14 children. Plasma ghrelin levels were measured using a commercial radioimmunoassay kit. The saliva ghrelin measurements were performed using a Human-ghrelin-radioimmunoassay-sensitive kit. Ghrelin levels in blood and saliva were found significantly lower in the rickets group compared to the healthy subjects in this study. Findings of this study shows that there is a relationship between ghrelin and the development of rickets. Decreased ghrelin levels may have caused to poor infant appetite and impaired nutritional status. Furthermore the absence of ghrelin's calciotropic effects may have contributed to the development of rickets. Detailed studies with larger series are warranted to support these findings.
Riketsli hastalarda ghrelin düzeyleri
Keywords: Ghrelin; rickets; vitamin D